A mildew-proof and crack-resistant FFC sanitary ceramic and a preparation method thereof
By applying a transparent antibacterial back bottom glaze layer to the bottom surface of FFC sanitary ceramics, the problem of mold and cracking during use of FFC sanitary ceramics is solved, and the effect of anti-mold and cracking is achieved.
Patent Information
- Application Number
- CN202411251755.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-09
AI Technical Summary
During use, FFC sanitary ceramics are prone to mold generation and cracking due to high water absorption. The existing technology has failed to effectively solve the problem of mold and cracking at the junction of the bottom surface.
Using a transparent antibacterial back bottom glaze layer, a mixture of quartz powder, kaolin, calcined alumina, potassium feldspar, wollastonite, nano zinc oxide, boron fuse and lithium carbonate is formed by applying a mixture of quartz powder, kaolin, calcined alumina, potassium feldspar, wollastonite, nano zinc oxide, boron fuse and lithium carbonate to form a low water absorption rate. The glaze layer is used to fill the sand hole and increase the bonding strength, preventing mold generation and cracking.
Effectively prevent mold production, improve the strength at the junction of the bottom surface, delay cracking and expansion, and ensure the crack resistance and aesthetics of FFC sanitary ceramics.
Smart Images

Figure CN118754725B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sanitary ceramics, and in particular to mildew-proof and crack-resistant FFC sanitary ceramics and a preparation method thereof. Background Art
[0002] Stoneware material, often referred to as FFC (abbreviation of Fine Fire Clay) in the sanitary ceramics industry, is a special material between pottery and porcelain. The water absorption rate of FFC is between 5% and 9%. Compared with the porcelain material with a water absorption rate of less than 0.5%, it has higher water absorption and certain air permeability, so FFC is often used to produce larger specifications or special shapes of sanitary ceramics (such as oversized basins, sinks and bathtubs, etc.), making FFC sanitary ceramics occupy a place in the field of sanitary ceramics.
[0003] Although FFC sanitary ceramics have shown their unique advantages in specific occasions, there are the following problems in the use of FFC sanitary ceramics: (1) Due to the high water absorption rate of FFC sanitary ceramics, during long-term use, the drain outlet is prone to the upward penetration of water in sewage under the action of capillaries, carrying nutrient-rich substances such as nitrogen and phosphorus and organic pollutants, resulting in mold easily forming at the junction between the bottom surface of FFC sanitary ceramics and its drain outlet, seriously affecting the appearance; (2) Due to the needs of structural design and production demoulding, the junction between the top surface of FFC sanitary ceramics and its drain outlet is usually an arc connection, while the junction between the bottom surface of FFC sanitary ceramics and its drain outlet is usually an angle connection, and the angle connection design easily leaves small sand holes at the junction of the bottom surface of the ceramics. At the same time, in a humid environment, the high water absorption rate of FFC material causes the bottom surface of FFC sanitary ceramics to easily expand due to moisture absorption, causing the sand holes at the bottom surface junction to gradually expand along the junction, which not only easily causes the bottom surface of FFC sanitary ceramics to crack, but also easily tears the top surface, causing the top surface to crack, affecting the product's appearance and service life.
[0004] In order to solve the above defects, since the bottom surface of FFC sanitary ceramics is not easily visible, it will not affect the aesthetics of the product. In addition, in the field of FFC sanitary ceramics, glaze is generally not applied to the bottom surface, so that in the prior art, a glaze layer is generally not set on the bottom surface of FFC sanitary ceramics, but only a smooth glaze is sprayed on the top surface of FFC sanitary ceramics and the intersection of the top surface to reduce moisture penetration. However, the blank with the bottom surface directly exposed is still easy to become a penetration channel for moisture and dirt, so that FFC sanitary ceramics still have the risk of mildew and cracking during use. Summary of the invention
[0005] The purpose of the present invention is to propose a method for preparing mildew-proof and crack-resistant FFC sanitary ceramics. The preparation method is simple and easy to operate. By adding a transparent antibacterial back glaze layer to fill the sand holes and protect the bottom joint of the FFC sanitary ceramic body, while ensuring the aesthetics, it can not only prevent the formation of mold, but also improve the strength of the bottom joint, avoid the cracking of the bottom joint during use and cause the FFC sanitary ceramics to crack, so as to meet the actual use needs.
[0006] Another object of the present invention is to provide a mildew-proof and crack-resistant FFC sanitary ceramic, which effectively solves the technical problem that the FFC sanitary ceramic is prone to mildew and cracking during use by adding a transparent antibacterial back glaze layer on the bottom surface of the sanitary ceramic.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] A method for preparing mildew-proof and crack-resistant FFC sanitary ceramics comprises the following steps:
[0009] A. preparing FFC sanitary ceramic slurry, and performing slip injection molding on the FFC sanitary ceramic slurry to obtain an FFC sanitary ceramic body;
[0010] B. Applying a transparent antibacterial back glaze to the bottom surface of the FFC sanitary ceramic body and the bottom intersection of the FFC sanitary ceramic body extending downward from 9 to 11 mm to obtain a transparent antibacterial back glaze layer; wherein, the transparent antibacterial back glaze comprises the following raw materials, calculated by weight: 24 to 28 parts of quartz powder, 7 to 12 parts of kaolin, 6 to 10 parts of calcined alumina, 6 to 12 parts of potassium feldspar, 12 to 16 parts of wollastonite, 12 to 15 parts of nano zinc oxide, 18 to 26 parts of boron frit and 0.8 to 1.5 parts of lithium carbonate;
[0011] C. Applying a surface glaze to the top surface of the FFC sanitary ceramic body and the area extending downward from the junction of the top surface of the FFC sanitary ceramic body by 15 to 20 mm to obtain a surface glaze layer;
[0012] D. After drying, the ceramic is put into a kiln for calcination to obtain mildew-proof and crack-resistant FFC sanitary ceramics; wherein the water absorption rate of the transparent antibacterial back glaze layer is less than 0.5%.
[0013] Further, in step B, calculated by mass percentage, the chemical composition of the boron frit includes SiO2 62-63%, Al2O3 10-11%, Fe2O3 0-0.01%, TiO2 0-0.01%, CaO 7-8%, MgO 0.8-1%, K2O 3-3.2%, Na2O 0.9-1.2%, ZrO2 0.2-0.5%, ZnO 1.5-1.8%, B2O3 10-11% and BaO 0.3-0.7%, and the rest is loss on ignition.
[0014] Furthermore, in step B, the particle size of the nano zinc oxide is 1 to 100 nm.
[0015] Furthermore, in step B, the preparation method of the transparent antibacterial back glaze is: after the raw materials of the transparent antibacterial back glaze are uniformly mixed according to the ratio, flower paper glue, sodium carboxymethyl cellulose, dispersant and water are added for ball milling, and the transparent antibacterial back glaze is obtained by sieving.
[0016] Furthermore, calculated by mass percentage, the amount of flower paper glue added is 2-4% of the amount of dry material added of the transparent antibacterial back glaze, the amount of sodium carboxymethyl cellulose added is 0.2-0.3% of the amount of dry material added of the transparent antibacterial back glaze, the amount of dispersant added is 0.35-0.45% of the amount of dry material added of the transparent antibacterial back glaze, and the amount of water added is 85-95% of the amount of dry material added of the transparent antibacterial back glaze.
[0017] Furthermore, in step B, the transparent antibacterial back glaze is applied by brushing, and according to mass percentage, the transparent antibacterial back glaze has a sieve residue of 0.2-0.8% on a 325-mesh sieve and a viscosity of 2300-3000 mPa·s.
[0018] Furthermore, in step B, a transparent antibacterial back glaze is applied to the bottom intersection of the FFC sanitary ceramic body, extending 90 to 110 mm around and 9 to 11 mm downward, to obtain a transparent antibacterial back glaze layer.
[0019] Furthermore, in step B, the thickness of the transparent antibacterial back glaze layer is 0.2 to 0.3 mm.
[0020] Furthermore, in step B, the specific gravity of the transparent antibacterial back glaze is 1.48 to 1.52.
[0021] A mildew-proof and crack-resistant FFC sanitary ceramic is prepared by using the method for preparing the mildew-proof and crack-resistant FFC sanitary ceramic.
[0022] The technical solution provided by the present invention may include the following beneficial effects:
[0023] 1. In this technical solution, the diffusion and dissolution of lithium oxide introduced by lithium carbonate, as well as the reduction of expansion coefficient by lithium carbonate, boron frit, nano zinc oxide, wollastonite, quartz powder and calcined alumina, combined with the suspension, plasticity, drying speed adjustment and calcination shrinkage performance of kaolin, ensure the filling effect of the transparent antibacterial back glaze layer on the sand holes at the junction of the bottom surface, improve the bonding strength of the transparent antibacterial back glaze layer, and avoid the risk of cracking of the transparent antibacterial back glaze layer during use. In addition, based on the low water absorption rate and good mechanical properties of the transparent antibacterial back glaze layer, it is conducive to improving the strength of the bottom surface junction, further avoiding the risk of cracking of the transparent antibacterial back glaze layer during use, so that the obtained FFC sanitary ceramics have excellent anti-cracking performance. In addition, the low water absorption rate of the transparent antibacterial back glaze layer is conducive to reducing hygroscopic expansion, so that even if cracks appear at the bottom, the expansion of the cracks can be delayed, thereby further ensuring the anti-cracking performance of the FFC sanitary ceramics.
[0024] 2. This technical solution improves the transparency of the transparent antibacterial back glaze through the interaction of silicon dioxide introduced by kaolin and quartz powder and boron trioxide introduced by boron frit. In addition, the density and stability of the glass phase network structure in this technical solution are increased, so that it can not only more effectively fill the sand holes at the junction of the bottom surface, improve the bonding strength, and prevent cracking, but also improve the gloss and smoothness of the transparent antibacterial back glaze layer, ensuring the performance of the product.
[0025] 3. In order to ensure the antibacterial effect, the present technical solution specifically prefers to add nano zinc oxide to the transparent antibacterial back glaze, which is conducive to obtaining a transparent antibacterial back glaze with a wider antibacterial range and stronger antibacterial ability. In addition, the transparent antibacterial back glaze layer can be used as a protective layer to seal the bottom surface of the FFC sanitary ceramic body, preventing the entry of external moisture. Furthermore, the water absorption rate of the transparent antibacterial back glaze layer is less than 0.5%, which reduces the hygroscopic expansion of the transparent antibacterial back glaze layer, prevents the entry of external moisture, and makes it impossible for mold to survive, thereby preventing the formation of mold. Therefore, the present technical solution is conducive to preventing the formation of mold through the mutual cooperation of nano zinc oxide and the sealing effect of the transparent antibacterial back glaze layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The cross-sectional schematic diagram of the mildew-proof and crack-resistant FFC sanitary ceramic of the present invention. DETAILED DESCRIPTION
[0027] The present technical solution provides a method for preparing mildew-proof and crack-resistant FFC sanitary ceramics, comprising the following steps:
[0028] A. preparing FFC sanitary ceramic slurry, and performing slip injection molding on the FFC sanitary ceramic slurry to obtain an FFC sanitary ceramic body;
[0029] B. Applying a transparent antibacterial back glaze to the bottom surface of the FFC sanitary ceramic body and the bottom intersection of the FFC sanitary ceramic body extending downward from 9 to 11 mm to obtain a transparent antibacterial back glaze layer; wherein, the transparent antibacterial back glaze comprises the following raw materials, calculated by weight: 24 to 28 parts of quartz powder, 7 to 12 parts of kaolin, 6 to 10 parts of calcined alumina, 6 to 12 parts of potassium feldspar, 12 to 16 parts of wollastonite, 12 to 15 parts of nano zinc oxide, 18 to 26 parts of boron frit and 0.8 to 1.5 parts of lithium carbonate;
[0030] C. Applying a surface glaze to the top surface of the FFC sanitary ceramic body and the area extending downward from the junction of the top surface of the FFC sanitary ceramic body by 15 to 20 mm to obtain a surface glaze layer;
[0031] D. After drying, the ceramic is put into a kiln for calcination to obtain mildew-proof and crack-resistant FFC sanitary ceramics; wherein the water absorption rate of the transparent antibacterial back glaze layer is less than 0.5%.
[0032] In order to solve the technical problem that the existing FFC sanitary ceramics are prone to mildew and cracking during use, this technical solution proposes a method for preparing mildew-proof and crack-resistant FFC sanitary ceramics, including four steps: A (preparing FFC sanitary ceramic blanks), B (applying transparent antibacterial back glaze), C (applying surface glaze) and D (firing in kiln). By adding a transparent antibacterial back glaze layer, the sand holes at the bottom surface intersection are filled and the bottom surface intersection of the FFC sanitary ceramic blank is protected. Under the premise of ensuring aesthetics, it can not only prevent the generation of mold, but also improve the strength of the bottom surface intersection, avoid cracking at the bottom surface intersection during use, and cause the FFC sanitary ceramics to crack, so as to meet the actual use needs. It should be noted that the FFC sanitary ceramic blank in this technical solution is formed by conventional FFC sanitary ceramic slurry grouting in the ceramic field, and the surface glaze layer is obtained by applying conventional surface glaze in the ceramic field. The FFC sanitary ceramic slurry and surface glaze are not further described here.
[0033] Specifically, the technical solution proposes a transparent antibacterial back glaze, the raw materials of which include quartz powder, kaolin, calcined alumina, potassium feldspar, wollastonite, nano zinc oxide, boron frit and lithium carbonate. First, the introduction of lithium carbonate can make the transparent antibacterial back glaze generate lithium oxide during the calcination process, and the lithium oxide diffuses into the sand holes at the junction of the bottom surface of the FFC sanitary ceramic body, and melts the silicon dioxide and aluminum oxide components in the FFC sanitary ceramic body. The melted silicon dioxide and aluminum oxide diffuse into the transparent antibacterial back glaze, so that the transparent antibacterial back glaze can not only fill the sand holes of the FFC sanitary ceramic body, but also react with the FFC sanitary ceramic body, which is beneficial to improve the bonding strength between the transparent antibacterial back glaze layer formed by the transparent antibacterial back glaze and the FFC sanitary ceramic body, and avoid cracking during the later use.
[0034] Secondly, when the expansion coefficient of the transparent antibacterial back glaze layer is greater than that of the FFC sanitary ceramic body, after cooling, the transparent antibacterial back glaze layer shrinks more than that of the FFC sanitary ceramic body, causing the transparent antibacterial back glaze layer to be subjected to tensile stress and prone to reticular cracks; when the expansion coefficient of the transparent antibacterial back glaze layer is less than that of the FFC sanitary ceramic body, after cooling, the transparent antibacterial back glaze layer shrinks less than that of the FFC sanitary ceramic body, causing the transparent antibacterial back glaze layer to be subjected to compressive stress and not prone to cracks. However, when the expansion coefficient of the transparent antibacterial back glaze layer is less than that of the FFC sanitary ceramic body, the difference exceeds (1 to 4) × 10 -6 / ℃, the compressive stress on the transparent antibacterial back glaze layer is too large, which will cause circular cracks or deglazing in the transparent antibacterial back glaze layer. That is, in order to avoid the risk of cracking of the transparent antibacterial back glaze layer in the later use process, the expansion coefficient of the transparent antibacterial back glaze layer needs to match the expansion coefficient of the FFC sanitary ceramic body.
[0035] In the prior art, the aluminum content in the FFC sanitary ceramic body exceeds 30%, and its thermal expansion coefficient is small. In order to match the thermal expansion coefficient of the transparent antibacterial back glaze layer, it is necessary to add a raw material that can reduce its expansion coefficient to the transparent antibacterial back glaze that forms the transparent antibacterial back glaze layer. The raw material commonly used to reduce the expansion coefficient in the prior art is zirconium silicate, but when zirconium silicate is added to the formula, due to the opacifying effect of zirconium silicate, it is easy to make the transparent antibacterial back glaze layer appear white. When the color of the FFC sanitary ceramic body is non-white, it is easy to cause color difference between the application place of the transparent antibacterial back glaze and the rest of the position, affecting the aesthetics. Therefore, this technical solution cannot reduce the expansion coefficient based on the above principle. It should be noted that the opacifying effect of zirconium silicate refers to the fact that zirconium silicate will form a crystal structure such as baddeleyite after the ceramic is fired. The above crystals scatter the incident light waves, making the ceramic glaze surface present an opacifying effect.
[0036] Therefore, in order to reduce the expansion coefficient of the transparent antibacterial back glaze, improve the thermal shock resistance, and avoid the risk of cracking during the later use, lithium carbonate, boron frit, nano zinc oxide, wollastonite, quartz powder and calcined alumina are added to the transparent antibacterial back glaze formula in this technical solution. Among them, the expansion coefficients of lithium carbonate, boron frit, nano zinc oxide, wollastonite, quartz powder and calcined alumina themselves are all low, which is beneficial to reducing the expansion coefficient of the transparent antibacterial back glaze; at the same time, boron frit can introduce boron trioxide, lithium carbonate can introduce lithium oxide, wollastonite can introduce calcium oxide, and potassium feldspar can introduce potassium oxide, that is, lithium carbonate, boron frit, nano zinc oxide and wollastonite all have a strong fluxing effect, which can promote the melting of high-temperature raw materials (quartz powder, kaolin and calcined alumina) in the transparent antibacterial back glaze, so that the transparent antibacterial back glaze can reach a molten state at a lower temperature, which is beneficial to further reduce the expansion coefficient of the transparent antibacterial back glaze. In addition, the silica in the quartz powder and kaolin in the transparent antibacterial back glaze and the aluminum oxide in the calcined alumina provide a network skeleton for the glass phase. When calcined, they react with the boron frit and wollastonite to form a boron aluminum silicate network structure (i.e., a glass phase network structure). Since the BO bond of the boron trioxide introduced by the boron frit has a high bond strength, it is beneficial to make the atomic arrangement in the glass network structure more orderly, improve the compactness of the glass phase network structure, and enable the transparent antibacterial back glaze to better resist the expansion of the volume when heated, thereby effectively reducing the thermal expansion coefficient. That is, in the technical solution, lithium carbonate, boron frit, nano zinc oxide, wollastonite, quartz powder and calcined alumina are all beneficial to reducing the thermal expansion coefficient of the transparent antibacterial back glaze, but the boron frit has the most obvious effect in reducing the expansion coefficient of the transparent antibacterial back glaze. Therefore, the technical solution limits the addition amount of the boron frit to 18 to 26 parts, ensuring that the transparent antibacterial back glaze has a low expansion coefficient matching the FFC sanitary ceramic body at a lower cost. It should be noted that, since albite increases the expansion coefficient of the glaze, albite cannot be added as a flux in the present technical solution. In addition, since boric acid is soluble in water, has a large loss on ignition, and affects the thixotropic properties of the glaze, the present technical solution cannot introduce boron trioxide through boric acid.
[0037] Furthermore, the suspension and plasticity of kaolin are conducive to reducing the cracking of the transparent antibacterial back glaze layer during the drying process. At the same time, kaolin can also adjust the drying speed of the transparent antibacterial back glaze layer to a certain extent, so that it matches the drying speed of the FFC sanitary ceramic body, thereby further reducing the risk of cracking. In addition, kaolin will shrink to a certain extent during the firing process. The above shrinkage characteristics enable the transparent antibacterial back glaze layer to better adapt to the shrinkage changes of the FFC sanitary ceramic body, improve the bonding strength between the two, and reduce the risk of the transparent antibacterial back glaze layer falling off. In addition, the silica in quartz powder and kaolin reacts with aluminum oxide in calcined alumina to form mullite, which is conducive to improving the mechanical properties and thermal stability of the transparent antibacterial back glaze layer.
[0038] Therefore, in the technical solution, the diffusion and melting of lithium oxide introduced by lithium carbonate, as well as the reduction of expansion coefficient by lithium carbonate, boron frit, nano zinc oxide, wollastonite, quartz powder and calcined alumina, combined with the suspension, plasticity, drying speed adjustment and calcination shrinkage performance of kaolin, ensure the filling effect of the transparent antibacterial back glaze layer on the sand holes at the junction of the bottom surface, improve the bonding strength of the transparent antibacterial back glaze layer, and avoid the risk of cracking of the transparent antibacterial back glaze layer during use. In addition, based on the low water absorption rate and good mechanical properties of the transparent antibacterial back glaze layer, it is conducive to improving the strength of the bottom surface junction, further avoiding the risk of cracking of the transparent antibacterial back glaze layer during use, so that the obtained FFC sanitary ceramics have excellent anti-cracking performance. In addition, the low water absorption rate of the transparent antibacterial back glaze layer is conducive to reducing hygroscopic expansion, so that even if cracks appear at the bottom, the expansion of the cracks can be delayed, thereby further ensuring the anti-cracking performance of the FFC sanitary ceramics.
[0039] Secondly, as the density and stability of the glass phase network structure are higher, the possibility of light scattering is lower, and the transparency of the glaze layer is higher. The strength of the silicon-oxygen bond (Si-O bond) of silica in the technical solution is relatively high, so that the compactness and stability of the formed glass phase network structure are relatively high; in addition, the boron trioxide introduced by the boron frit is conducive to increasing the density and stability of the glass phase network structure. Therefore, the technical solution improves the transparency of the transparent antibacterial back glaze through the mutual cooperation of silica introduced by kaolin and quartz powder and boron trioxide introduced by the boron frit. In addition, the increase in the density and stability of the glass phase network structure in the technical solution can not only more effectively fill the sand holes at the junction of the bottom surface, improve the bonding strength, and prevent cracking, but also improve the gloss and smoothness of the transparent antibacterial back glaze layer, ensuring the performance of the product.
[0040] Again, the inorganic antibacterial agents added to the glaze in the prior art are mainly nanosilver and nanocopper oxide. Nanosilver easily reacts with oxygen in the air to generate silver oxide during the high-temperature calcination of the glaze, and silver oxide easily volatilizes and cannot be effectively integrated into the glaze layer; the high melting point of nanosilver makes it difficult to evenly distribute in the glaze, and it is easy to produce pores or cracks during the calcination process, affecting the quality of the product. Nanocopper oxide is black. When it is added to the glaze formula, it is easy to make the color of the glaze darker, and it is easy to block the original color of the FFC sanitary ceramic body, resulting in inconsistent color between the application area and the rest of the FFC sanitary ceramic body, resulting in color deviation, affecting the aesthetics of the product. Therefore, neither nanosilver nor nanocopper oxide can be added to the present technical solution as antibacterial agents.
[0041] When nano zinc oxide comes into contact with bacteria, it can release ions. High concentrations of zinc ions can destroy the internal environment of the bacteria, causing damage to the bacterial cell wall, and then destroying the inherent morphology of the cell. At the same time, zinc ions can also bind to active proteases in bacteria, making them inactive, thereby blocking the life activities of bacteria and achieving a bactericidal effect. In addition, the small size effect of nano zinc oxide also enables it to more easily penetrate the cell wall and cell membrane of bacteria, directly acting on the inside of the bacteria, making it have a better antibacterial effect than ordinary zinc oxide. Therefore, in order to ensure the antibacterial effect, the technical solution specifically preferably adds nano zinc oxide to the transparent antibacterial back glaze, which is conducive to obtaining a transparent antibacterial back glaze with a wider antibacterial range and stronger antibacterial ability. In addition, since the color of nano zinc oxide is light yellow, and it can achieve a good antibacterial effect at a relatively small addition amount (12 to 15 parts), nano zinc oxide will not change the transparency of the transparent antibacterial back glaze, avoiding the inconsistency of color between the application area and the rest of the FFC sanitary ceramic body, which affects the appearance of the product.
[0042] In addition, the transparent antibacterial back glaze layer can be used as a protective layer to seal the bottom surface of the FFC sanitary ceramic body, preventing the entry of external moisture. Furthermore, the water absorption rate of the transparent antibacterial back glaze layer is less than 0.5%, which reduces the hygroscopic expansion of the transparent antibacterial back glaze layer, prevents the entry of external moisture, and makes it impossible for mold to survive, thereby preventing the formation of mold. Therefore, the technical solution is conducive to preventing the formation of mold through the mutual cooperation of nano zinc oxide and the sealing effect of the transparent antibacterial back glaze layer.
[0043] Finally, according to the weight percentage, the transparent antibacterial back glaze includes the following raw materials: 24-28 parts of quartz powder, 7-12 parts of kaolin, 6-10 parts of calcined alumina, 6-12 parts of potassium feldspar, 12-16 parts of wollastonite, 12-15 parts of nano zinc oxide, 18-26 parts of boron frit and 0.8-1.5 parts of lithium carbonate. When the addition amount of kaolin is less than 7 parts, the transparent antibacterial back glaze is easy to fall off and powder due to its low strength; when the addition amount of kaolin is greater than 12 parts, the transparent antibacterial back glaze is too high in strength, has high viscosity and is too moisturizing, resulting in poor uniformity of application. When the addition amount of lithium carbonate is higher than 1.5 parts, the melting temperature of the transparent antibacterial back glaze is too low and it is easy to bubble. When the addition amount of lithium carbonate is less than 0.8 parts, the high-temperature flow of the transparent antibacterial back glaze is poor, which makes it easy to be fired into a difficult-to-melt flat surface.
[0044] It should be noted that in the preparation process of FFC sanitary ceramic blanks, if the FFC sanitary ceramic blanks are dried first and then the transparent antibacterial back glaze is applied, since the transparent antibacterial back glaze has a high water content, it is necessary to dry again after applying the transparent antibacterial back glaze with a high water content, which not only increases the production process but also leads to energy waste. Therefore, the present technical scheme does not perform drying in the process of preparing the FFC sanitary ceramic blanks, but only performs drying before entering the kiln for calcination, which is beneficial to improving production efficiency and reducing production costs.
[0045] In addition, the glaze is applied to the top surface of the FFC sanitary ceramic body and the range of 15 to 20 mm extending downward from the top surface intersection of the FFC sanitary ceramic body. Figure 1 The range of the FFC sanitary ceramic body (shown in a) is also protected to prevent moisture from entering the sand holes at the bottom surface intersection from the top surface through the inside of the FFC sanitary ceramic body, thereby further preventing the FFC sanitary ceramic from cracking and mildewing. Furthermore, the height of the drain is generally 20 to 30 mm, and a sealing ring needs to be installed at a height of 9 to 11 mm from the intersection of the drain and the bottom surface of the FFC sanitary ceramic body. Therefore, the downward extension range of the bottom surface intersection is limited to 9 to 11 mm (as shown in a). Figure 1 As shown in b), since the FFC sanitary ceramic body has a certain thickness, in order to ensure the consistent height of the glaze applied inside and outside the drain, the downward extension range of the top surface intersection must be higher than the downward extension range of the bottom surface intersection.
[0046] It should be further explained that the bottom surface intersection of the FFC sanitary ceramic body refers to the intersection of the bottom surface of the FFC sanitary ceramic body and its drain outlet (such as Figure 1 The top surface intersection of the FFC sanitary ceramic body refers to the intersection of the top surface of the FFC sanitary ceramic body and its drain outlet (as shown in Figure 1 (shown at d in the figure).
[0047] Further description, in step B, calculated by mass percentage, the chemical composition of the boron frit includes SiO2 62-63%, Al2O3 10-11%, Fe2O3 0-0.01%, TiO2 0-0.01%, CaO 7-8%, MgO 0.8-1%, K2O 3-3.2%, Na2O 0.9-1.2%, ZrO2 0.2-0.5%, ZnO 1.5-1.8%, B2O3 10-11% and BaO 0.3-0.7%, and the rest is loss on ignition.
[0048] The technical solution preferably adds a boron frit with a B2O3 content of 10-11% calculated by mass percentage to the transparent antibacterial back glaze raw material, which helps to increase the B2O3 content in the formula, so as to achieve the requirements of low expansion coefficient, high gloss and high transparency. At the same time, the SiO2 content in the boron frit is as high as 60% or more, and the Al2O3 content is as high as 10%, which is conducive to increasing the content of silicon and aluminum in the formula, and improving the mechanical properties of the transparent antibacterial back glaze raw material while ensuring the fluxing effect of the boron frit.
[0049] Preferably, calculated by mass percentage, the chemical composition of the boron frit includes SiO2 62.58%, Al2O3 10.54%, Fe2O3 0.01%, TiO2 0.01%, CaO 7.70%, MgO 0.88%, K2O 3.14%, Na2O 0.98%, ZrO2 0.30%, ZnO 1.71%, B2O3 10.98% and BaO 0.50%, and the rest is loss on ignition.
[0050] Further description: in step B, the particle size of the nano zinc oxide is 1 to 100 nm.
[0051] Due to its volumetric efficiency and high dispersibility, the fluxing effect of nano zinc oxide with a particle size of 1 to 100 nm is 30-50% higher than that of ordinary zinc oxide. In addition, the size of nano zinc oxide with a particle size of 1 to 100 nm is between atomic clusters and macroscopic particles, which makes it have the characteristics of stable antibacterial performance, wide antibacterial range, strong antibacterial ability, and the antibacterial performance is 2 to 3 times higher than that of ordinary zinc oxide. Therefore, the technical solution is beneficial to improve its antibacterial properties and fluxing effect by adding nano zinc oxide with a particle size of 1 to 100 nm to the transparent antibacterial back glaze raw material, thereby ensuring the performance of the transparent antibacterial back glaze raw material.
[0052] Further, in step B, the preparation method of the transparent antibacterial back glaze is: after the raw materials of the transparent antibacterial back glaze are uniformly mixed according to the ratio, flower paper glue, sodium carboxymethyl cellulose, dispersant and water are added for ball milling, and the transparent antibacterial back glaze is obtained by sieving.
[0053] Flower paper glue is a polymer adhesive, the main component of which is acrylic polymer, and has good bonding ability. Adding it to the transparent antibacterial back glaze formula is conducive to increasing the adhesion of the transparent antibacterial back glaze to the FFC sanitary ceramic body, and preventing it from falling off during the application process and affecting the performance of the product. It should be noted that the manufacturer of the flower paper glue in this technical solution is Dongguan Qiaotou Yitai Silk Screen Material Business Department, model number is YT-650.
[0054] Furthermore, sodium carboxymethyl cellulose can ensure the dispersibility of the flower paper glue, so that the glaze slurry is always in a stable dispersed state, avoiding glaze slurry stratification; at the same time, sodium carboxymethyl cellulose has good moisturizing properties, which can prevent the water in the transparent antibacterial back glaze from evaporating too quickly during the drying process, causing a large difference in moisture inside and outside the product and cracking, thereby ensuring the quality of the product. In addition, the dispersant can significantly improve the dispersibility of the transparent antibacterial back glaze, so that the high-concentration transparent antibacterial back glaze can be effectively diluted by water, reducing its viscosity and improving its fluidity, which is not only conducive to improving the construction performance of the glaze, but also conducive to ensuring that the transparent antibacterial back glaze can be evenly applied to form a smooth and flat glaze layer, thereby improving the appearance quality and performance of the product.
[0055] Preferably, the dispersant is sodium polyacrylate. Sodium polyacrylate has excellent dispersibility and can be effectively adsorbed on the surface of raw material particles in the transparent antibacterial back glaze. Through the extension and entanglement of its polymer chain, a steric hindrance effect is formed to prevent the raw material particles from approaching and agglomerating each other. At the same time, sodium polyacrylate can also form hydrogen bonds with water molecules, increase the hydrophilicity of the surface of the raw material particles, and further promote the dispersion of the raw material particles in the transparent antibacterial back glaze.
[0056] Further description, calculated by mass percentage, the amount of flower paper glue added is 2-4% of the amount of dry material added of the transparent antibacterial back glaze, the amount of sodium carboxymethyl cellulose added is 0.2-0.3% of the amount of dry material added of the transparent antibacterial back glaze, the amount of dispersant added is 0.35-0.45% of the amount of dry material added of the transparent antibacterial back glaze, and the amount of water added is 85-95% of the amount of dry material added of the transparent antibacterial back glaze.
[0057] By limiting the addition amount of flower paper glue, sodium carboxymethyl cellulose, dispersant and water, it is helpful to ensure the performance of transparent antibacterial back glaze, and then ensure the performance of FFC sanitary ceramics.
[0058] Further, in step B, the transparent antibacterial back glaze is applied by brushing, and according to mass percentage, the transparent antibacterial back glaze has a sieve residue of 0.2-0.8% on a 325-mesh sieve and a viscosity of 2300-3000 mPa·s.
[0059] Since the bottom surface of FFC sanitary ceramics is less regular and the construction area is relatively small, this technology uses a brushing method to apply a transparent antibacterial back glaze to ensure the convenience and low cost of construction.
[0060] Furthermore, since brush marks are unavoidable during the painting process, if the viscosity of the transparent antibacterial backing glaze is too low and the high-temperature fluidity is too poor, brush marks will be produced on the transparent antibacterial backing glaze layer after calcination. Therefore, the present technical solution preferably uses a transparent antibacterial backing glaze with a viscosity of 2300-3000 mPa·s and good high-temperature fluidity to ensure that the transparent antibacterial backing glaze layer after high-temperature sintering is smoothly spread out without brush marks.
[0061] In addition, by optimizing the fineness of the transparent antibacterial back glaze, the transparent antibacterial back glaze layer formed by the transparent antibacterial back glaze is easier to melt, thereby obtaining a delicate and smooth glaze surface, making it difficult for stains to be adsorbed, and improving the anti-fouling ability. However, when the fineness of the transparent antibacterial back glaze is too low, glaze shrinkage is likely to occur. Therefore, the technical solution limits the fineness of the transparent antibacterial back glaze to 0.2-0.8% of the sieve residue after passing through a 325-mesh sieve to ensure its performance.
[0062] To further illustrate, in step B, a transparent antibacterial back glaze is applied to the bottom intersection of the FFC sanitary ceramic body, extending 90 to 110 mm around and 9 to 11 mm downward, to obtain a transparent antibacterial back glaze layer.
[0063] The mold mainly extends around the bottom of the FFC sanitary ceramic body, 90 to 110 mm (such as Figure 1 e), extending downward by 9 to 11 mm (as shown in Figure 1 Therefore, the technical solution is conducive to solving the mildew problem at a lower cost by optimizing the application position of the transparent antibacterial back glaze, and filling the sand holes to avoid cracking problems in the later use process, so as to meet the actual use needs.
[0064] Further description, in step B, the thickness of the transparent antibacterial back glaze layer is 0.2-0.3 mm.
[0065] When the transparent antibacterial back glaze layer is too thin, it is not easy to cover the bottom surface of the FFC sanitary ceramic body, and leakage is likely to occur, affecting the performance of the obtained FFC sanitary ceramic. When the transparent antibacterial back glaze layer is too thick, it is easy to increase the production cost, and when the transparent antibacterial back glaze layer is too thick, the number of glazing times required also increases, further increasing the production cost.
[0066] Further description, in step B, the specific gravity of the transparent antibacterial back glaze is 1.48-1.52.
[0067] When the specific gravity of the transparent antibacterial back glaze is too high, the glaze will be too thick and the fluidity will be poor, which will make the application uniformity of the transparent antibacterial back glaze poor and easily form defects such as glaze roads. In addition, the high specific gravity of the transparent antibacterial back glaze will easily hinder the discharge of gas and water generated during the calcination process of the transparent antibacterial back glaze, causing the glaze layer obtained by calcining the transparent antibacterial back glaze to crack easily; when the specific gravity of the transparent antibacterial back glaze is too low, the fluidity of the transparent antibacterial back glaze is too good, and it is easy to flow during the glazing process, which also causes the application uniformity of the transparent antibacterial back glaze to be poor and easily form defects such as glaze roads. It should be noted that the glaze road refers to the glaze layer being thicker in some areas and thinner or missing in other areas.
[0068] A mildew-proof and crack-resistant FFC sanitary ceramic is prepared by using the method for preparing the mildew-proof and crack-resistant FFC sanitary ceramic.
[0069] A mildew-proof and crack-resistant FFC sanitary ceramic prepared by the above-mentioned mildew-proof and crack-resistant FFC sanitary ceramic preparation method effectively solves the technical problem that the FFC sanitary ceramic is prone to mildew and cracking during use by adding a transparent antibacterial back glaze layer on the bottom surface of the sanitary ceramic.
[0070] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0071] Performance Testing
[0072] Anti-mildew performance: Put the anti-mildew and anti-cracking FFC sanitary ceramics into tap water for 30 days, and observe whether there is mildew on the anti-mildew and anti-cracking FFC sanitary ceramics. If there is no mildew, the anti-mildew performance is qualified.
[0073] Anti-cracking performance: Place the mildew-proof and crack-resistant FFC sanitary ceramics into an autoclave, gradually increase the pressure in the test area of the autoclave to 20KPa, and maintain it for 30 minutes, and observe whether the mildew-proof and crack-resistant FFC sanitary ceramics have cracking phenomena. If there is no cracking phenomenon, the anti-cracking performance is qualified.
[0074] Glossiness: Use a gloss meter to test the glossiness of the bottom glaze of FFC sanitary ceramics.
[0075] Glaze effect: Observe the bottom glaze of FFC sanitary ceramics with the naked eye.
[0076] Example 1
[0077] A. preparing FFC sanitary ceramic slurry, and performing slip injection molding on the FFC sanitary ceramic slurry to obtain an FFC sanitary ceramic body;
[0078] B. Apply a transparent antibacterial back glaze having a sieve residue of 0.5% on a 325-mesh sieve, a viscosity of 2500 Pa·s, and a specific gravity of 1.48 to the bottom surface of the FFC sanitary ceramic body and the bottom intersection of the FFC sanitary ceramic body extending downward by 9 mm to obtain a transparent antibacterial back glaze layer with a thickness of 0.2 mm; the preparation method of the transparent antibacterial back glaze is as follows: 28 parts of quartz powder, 7 parts of kaolin, 8 parts of calcined alumina, 6 parts of potassium feldspar, 13 parts of wollastonite, 15 parts of nano zinc oxide with a particle size of 20 nm, 22 parts of boron frit, and 1 part of lithium carbonate are uniformly mixed, and then flower paper glue and carboxymethyl cellulose are added; Sodium, sodium polyacrylate and water are ball-milled and sieved to obtain a transparent antibacterial back glaze; calculated by mass percentage, the amount of flower paper glue added is 3% of the amount of dry material added of the transparent antibacterial back glaze, the amount of sodium carboxymethyl cellulose added is 0.3% of the amount of dry material added of the transparent antibacterial back glaze, the amount of sodium polyacrylate added is 0.4% of the amount of dry material added of the transparent antibacterial back glaze, and the amount of water added is 90% of the amount of dry material added of the transparent antibacterial back glaze; calculated by mass percentage, the chemical composition of the boron frit includes SiO2 62.58%, Al2O3 10.54%, Fe2O3 0.01%, TiO2 0.01%, CaO 7.70%, MgO 0.88%, K2O 3.14%, Na2O 0.98%, ZrO2 0.30%, ZnO 1.71%, B2O3 10.98% and BaO 0.50%, and the rest is ignition loss.
[0079] C. Applying the surface glaze to the top surface of the FFC sanitary ceramic body and the area extending downward by 15 mm from the intersection of the top surface of the FFC sanitary ceramic body to obtain a surface glaze layer;
[0080] D. After drying, the product is put into a kiln for calcination to obtain mildew-proof and crack-resistant FFC sanitary ceramics; wherein the water absorption rate of the transparent antibacterial back glaze layer is 0.3%.
[0081] Example 2
[0082] A. preparing FFC sanitary ceramic slurry, and performing slip injection molding on the FFC sanitary ceramic slurry to obtain an FFC sanitary ceramic body;
[0083] B. Apply a transparent antibacterial back glaze having a sieve residue of 0.2% on a 325-mesh sieve, a viscosity of 2300 mPa·s, and a specific gravity of 1.48 to the bottom surface of the FFC sanitary ceramic body and the bottom intersection of the FFC sanitary ceramic body extending downward by 11 mm to obtain a transparent antibacterial back glaze layer with a thickness of 0.3 mm; the preparation method of the transparent antibacterial back glaze is as follows: 24 parts of quartz powder, 12 parts of kaolin, 6.5 parts of calcined alumina, 10 parts of potassium feldspar, 16 parts of wollastonite, 12 parts of nano zinc oxide with a particle size of 50 nm, 18 parts of boron frit, and 1.5 parts of lithium carbonate, and then add flower paper glue, carboxymethyl Sodium cellulose, sodium polyacrylate and water are ball-milled and sieved to obtain a transparent antibacterial back glaze; calculated by mass percentage, the amount of flower paper glue added is 2% of the amount of dry material added of the transparent antibacterial back glaze, the amount of sodium carboxymethyl cellulose added is 0.3% of the amount of dry material added of the transparent antibacterial back glaze, the amount of sodium polyacrylate added is 0.45% of the amount of dry material added of the transparent antibacterial back glaze, and the amount of water added is 85% of the amount of dry material added of the transparent antibacterial back glaze; calculated by mass percentage, the chemical composition of the boron frit includes SiO2 62.58%, Al2O3 10.54%, Fe2O3 0.01%, TiO2 0.01%, CaO 7.70%, MgO 0.88%, K2O 3.14%, Na2O 0.98%, ZrO2 0.30%, ZnO 1.71%, B2O3 10.98% and BaO 0.50%, and the rest is ignition loss.
[0084] C. Applying the surface glaze to the top surface of the FFC sanitary ceramic body and the area extending downward from the junction of the top surface of the FFC sanitary ceramic body by 17 mm to obtain a surface glaze layer;
[0085] D. After drying, the ceramic is put into a kiln for calcination to obtain mildew-proof and crack-resistant FFC sanitary ceramics; wherein the water absorption rate of the transparent antibacterial back glaze layer is 0.4%.
[0086] Example 3
[0087] A. preparing FFC sanitary ceramic slurry, and performing slip injection molding on the FFC sanitary ceramic slurry to obtain an FFC sanitary ceramic body;
[0088] B. Apply a transparent antibacterial back glaze having a sieve residue of 0.8% on a 325-mesh sieve, a viscosity of 3000 mPa·s, and a specific gravity of 1.52 to the bottom of the FFC sanitary ceramic body, extending 90 to 110 mm around the junction and 11 mm downward, to obtain a transparent antibacterial back glaze layer with a thickness of 0.3 mm; the preparation method of the transparent antibacterial back glaze is as follows: 25 parts of quartz powder, 7 parts of kaolin, 9.2 parts of calcined alumina, 8 parts of potassium feldspar, 12 parts of wollastonite, 12 parts of nano zinc oxide with a particle size of 100 nm, 26 parts of boron frit, and 0.8 parts of lithium carbonate are mixed evenly, and then flower paper glue and carboxymethyl fiber are added. Sodium cellulose, sodium polyacrylate and water are ball-milled and sieved to obtain a transparent antibacterial back glaze; calculated by mass percentage, the amount of flower paper glue added is 4% of the amount of dry materials added to the transparent antibacterial back glaze, the amount of sodium carboxymethyl cellulose added is 0.2% of the amount of dry materials added to the transparent antibacterial back glaze, the amount of sodium polyacrylate added is 0.35% of the amount of dry materials added to the transparent antibacterial back glaze, and the amount of water added is 85-95% of the amount of dry materials added to the transparent antibacterial back glaze; calculated by mass percentage, the chemical composition of the boron frit includes SiO2 62.58%, Al2O3 10.54%, Fe2O3 0.01%, TiO2 0.01%, CaO 7.70%, MgO 0.88%, K2O 3.14%, Na2O 0.98%, ZrO2 0.30%, ZnO 1.71%, B2O3 10.98% and BaO 0.50%, and the rest is ignition loss.
[0089] C. Applying the surface glaze to the top surface of the FFC sanitary ceramic body and the area extending 20 mm downward from the intersection of the top surface of the FFC sanitary ceramic body to obtain a surface glaze layer;
[0090] D. After drying, the product is put into a kiln for calcination to obtain mildew-proof and crack-resistant FFC sanitary ceramics; wherein the water absorption rate of the transparent antibacterial back glaze layer is 0.3%.
[0091] Comparative Example 1
[0092] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that Comparative Example 1 does not have step B.
[0093] Comparative Example 2
[0094] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that lithium carbonate is not added to the transparent antibacterial back glaze formula in Comparative Example 2.
[0095] Comparative Example 3
[0096] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 1, except that no boron frit is added to the formula of the transparent antibacterial back glaze in Comparative Example 3.
[0097] The performance tests of the mildew-proof and crack-resistant FFC sanitary ceramics prepared by the preparation methods of Examples 1-3 and Comparative Examples 1-3 were respectively carried out, and the results are shown in Table 1:
[0098] Table 1 Performance test results of different mildew and crack resistant FFC sanitary ceramics in the examples and comparative examples
[0099]
[0100] It can be seen from the performance test results in Table 1 that the mildew-proof and crack-resistant FFC sanitary ceramics obtained by the present technical solution can not only prevent the formation of mold, but also improve the strength of the bottom surface joint while ensuring aesthetics, by adding a transparent antibacterial back glaze layer to fill the sand holes and protect the bottom surface joint of the FFC sanitary ceramic body, thereby avoiding cracking of the bottom surface joint during use and causing cracking of the FFC sanitary ceramics, thereby meeting actual use needs.
[0101] In Comparative Example 1, since step B was not provided, mildew and cracking occurred.
[0102] In Comparative Example 2, since lithium carbonate was not added, not only was the transparent antibacterial back glaze layer limited in filling the sand holes at the junction of the bottom surface of the FFC sanitary ceramic body, but also the bonding strength with the FFC sanitary ceramic body was reduced, resulting in a slight risk of cracking, so that external moisture could easily enter the interior of the FFC sanitary ceramic body, so that even if the transparent antibacterial back glaze layer had an antibacterial effect, it would still cause slight mildew. In addition, since lithium carbonate was not added, the high-temperature flowability of the transparent antibacterial back glaze was poor, making it difficult to melt flat after calcination, and the flatness of the glaze surface was poor.
[0103] In Comparative Example 3, since no boron frit is added, the expansion coefficient of the transparent antibacterial back glaze layer formed after calcination is lower than the expansion coefficient of the FFC sanitary ceramic body, resulting in a slight risk of cracking, making it easy for external moisture to enter the interior of the FFC sanitary ceramic body, so that even if the transparent antibacterial back glaze layer has an antibacterial effect, it still causes slight mildew.
[0104] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A method for preparing mildew-proof and crack-resistant FFC sanitary ceramics, characterized in that: The following steps are involved: A. preparing FFC sanitary ceramic slurry, and performing slip injection molding on the FFC sanitary ceramic slurry to obtain an FFC sanitary ceramic body; B. Applying a transparent antibacterial back glaze to the bottom surface of the FFC sanitary ceramic body and the bottom intersection of the FFC sanitary ceramic body extending downward from 9 to 11 mm to obtain a transparent antibacterial back glaze layer; wherein, the transparent antibacterial back glaze is composed of the following raw materials, calculated by weight: 24 to 28 parts of quartz powder, 7 to 12 parts of kaolin, 6 to 10 parts of calcined alumina, 6 to 12 parts of potassium feldspar, 12 to 16 parts of wollastonite, 12 to 15 parts of nano zinc oxide, 18 to 26 parts of boron frit and 0.8 to 1.5 parts of lithium carbonate; Calculated by mass percentage, the chemical composition of the boron frit includes SiO2 62-63%, Al2O3 10-11%, Fe2O30-0.01%, TiO2 0-0.01%, CaO 7-8%, MgO 0.8-1%, K2O 3-3.2%, Na2O 0.9-1.2%, ZrO2 0.2-0.5%, ZnO 1.5-1.8%, B2O3 10-11% and BaO 0.3-0.7%, and the rest is ignition loss; C. Applying a surface glaze to the top surface of the FFC sanitary ceramic body and the area extending downward from the junction of the top surface of the FFC sanitary ceramic body by 15 to 20 mm to obtain a surface glaze layer; D. After drying, the ceramic is put into a kiln for calcination to obtain mildew-proof and crack-resistant FFC sanitary ceramics; wherein the water absorption rate of the transparent antibacterial back glaze layer is less than 0.5%.
2. The method for preparing mildew-proof and crack-resistant FFC sanitary ceramics according to claim 1, characterized in that: In step B, the particle size of the nano zinc oxide is 1 to 100 nm.
3. The method for preparing mildew-proof and crack-resistant FFC sanitary ceramics according to claim 1, characterized in that: In step B, the preparation method of the transparent antibacterial back glaze is: after the raw materials of the transparent antibacterial back glaze are uniformly mixed according to the proportion, flower paper glue, sodium carboxymethyl cellulose, dispersant and water are added for ball milling, and the transparent antibacterial back glaze is obtained by sieving.
4. The method for preparing mildew-proof and crack-resistant FFC sanitary ceramics according to claim 3, characterized in that: Calculated by mass percentage, the amount of flower paper glue added is 2-4% of the amount of dry material added of the transparent antibacterial back glaze, the amount of sodium carboxymethyl cellulose added is 0.2-0.3% of the amount of dry material added of the transparent antibacterial back glaze, the amount of dispersant added is 0.35-0.45% of the amount of dry material added of the transparent antibacterial back glaze, and the amount of water added is 85-95% of the amount of dry material added of the transparent antibacterial back glaze.
5. The method for preparing mildew-proof and crack-resistant FFC sanitary ceramics according to claim 1, characterized in that: In step B, the transparent antibacterial back glaze is applied by brushing, and according to mass percentage, the transparent antibacterial back glaze has a sieve residue of 0.2-0.8% on a 325-mesh sieve and a viscosity of 2300-3000 mPa·s.
6. The method for preparing mildew-proof and crack-resistant FFC sanitary ceramics according to claim 1, characterized in that: In step B, a transparent antibacterial back glaze is applied to the bottom intersection of the FFC sanitary ceramic body, extending 90 to 110 mm around and 9 to 11 mm downward, to obtain a transparent antibacterial back glaze layer.
7. The method for preparing mildew-proof and crack-resistant FFC sanitary ceramics according to claim 1, characterized in that: In step B, the thickness of the transparent antibacterial back glaze layer is 0.2-0.3 mm.
8. The method for preparing mildew-proof and crack-resistant FFC sanitary ceramics according to claim 1, characterized in that: In step B, the specific gravity of the transparent antibacterial back glaze is 1.48-1.
52.
9. A mildew-proof and crack-resistant FFC sanitary ceramic, characterized in that: The anti-mildew and anti-cracking FFC sanitary ceramics are prepared using the preparation method of any one of claims 1 to 8.
